2021
DOI: 10.1371/journal.pone.0257265
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive integrated post-GWAS analysis of Type 1 diabetes reveals enhancer-based immune dysregulation

Abstract: Type 1 diabetes (T1D) is an organ-specific autoimmune disease, whereby immune cell-mediated killing leads to loss of the insulin-producing β cells in the pancreas. Genome-wide association studies (GWAS) have identified over 200 genetic variants associated with risk for T1D. The majority of the GWAS risk variants reside in the non-coding regions of the genome, suggesting that gene regulatory changes substantially contribute to T1D. However, identification of causal regulatory variants associated with T1D risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…In contrast to Type 1 Diabetes (T1D) were the majority of genetic association signals exert their effect through the immune system (Kim et al, 2021), there is compelling evidence fromphysiology (De Franco, 2020; Dimas et al, 2014) and epigenomics (Thurner et al, 2018) that pancreatic islets are a key tissue mediating a large proportion of the genetic risk for type 2 diabetes (T2D). T2D is a complex disease with multiple associated genetic risk loci identified through genome-wide association studies (GWAS) have identified >700 signals (Mahajan et al, 2018), the majority of which signals are located in non-coding regions of the genome with a presumed regulatory function (Mahajan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to Type 1 Diabetes (T1D) were the majority of genetic association signals exert their effect through the immune system (Kim et al, 2021), there is compelling evidence fromphysiology (De Franco, 2020; Dimas et al, 2014) and epigenomics (Thurner et al, 2018) that pancreatic islets are a key tissue mediating a large proportion of the genetic risk for type 2 diabetes (T2D). T2D is a complex disease with multiple associated genetic risk loci identified through genome-wide association studies (GWAS) have identified >700 signals (Mahajan et al, 2018), the majority of which signals are located in non-coding regions of the genome with a presumed regulatory function (Mahajan et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 78 loci were found in 42 genes of long non-coding RNA; 13 of these 78 loci were located in enhancer regions, and among them, rs3129716 and rs886424 were highly likely to be the most significant enhancer SNPs. The authors inferred that most of the identified target genes played an important role in the immune response and regulation of activity of gene expression including HLA genes (6p21) [62].…”
Section: Multicenter and Genome-wide Association Studies (Gwas)mentioning
confidence: 99%
“…Moreover, another study showed that a risk allele within USF1 appeared to remove the inductive effect of insulin on USF1 expression, which in turn affected the expression of other target genes, contributing to increased risk of cardiometabolic diseases [75]. HLA-DMB was also reported to be associated with type 1 DM in several human genetic studies [76][77][78].…”
Section: Diabetes Mellitusmentioning
confidence: 99%